Kinerja Model Kotak Infiltrasi Pada Kondisi Tanah Jenuh dan Tidak Jenuh untuk Mengurangi Genangan di Jalan Perkotaan - Awliya Tribhuwana; Slamet Imam Wahyudi; Moh Faiqun Ni'am; Henny Pratiwi Adi (Department of Civil Engineering, Diponegoro University, 2025)
Flooding on road surfaces due to heavy rainfall is a major problem, especially in urban areas. This situation requires an infiltration-based control system in accordance with the Low Impact Development (LID) concept. The infiltration box model is one solution to reduce inundation around road medians. This study aims to realize the infiltration box model, analyze the flow behavior of the model in the road median, and compare the model's performance under saturated and unsaturated soil conditions. The research method was carried out experimentally using flow in a laboratory flume channel. Based on the road area and return rainfall for a 2-year period, a discharge model of 0.109 l/s was used. The parameters analyzed included runoff discharge, infiltration discharge, and the volume of the box reservoir. The results showed that under saturated soil conditions, runoff reached 74.69% of the rainfall discharge, while infiltration and reservoir were only 11.20% and 5.89%, respectively. Under unsaturated soil conditions, runoff decreased to 46.65%, while infiltration increased to 30.43% and the box reservoir to 12.78%. Infiltration discharge in unsaturated soil was recorded at approximately 2.7 times greater than in saturated soil. These results demonstrate the influence of soil water content on the infiltration box performance model. Infiltration boxes should be integrated with other road drainage systems, including water pipes running under the road to the roadside drains.